A prospective non-randomized interventional study of dynamic changes of L3SMI in patients with gastric cancer undergoing ambulatory chemotherapy with active nutrition combined with exercise - Shu-Rong Zhao; Xiao-Rong Li; Zhen-Hao Li; Xiao-Juan Ren; Ji-Xiang Hou; Jun Zhao; Gao-Wa Jin; Quan-Fu Li (Frontiers in Oncology)
ObjectiveTo compare the effects of combined active nutrition and exercise intervention based on a standard regimen on the dynamic changes in the L3 skeletal muscle index (L3SMI) of patients with gastric cancer receiving SOX/XELOX ambulatory chemotherapy, and explore its relationship with chemotherapy-related adverse reactions.MethodsThis prospective non-randomized interventional study was conducted on patients with gastric cancer who received adjuvant or first-line SOX/XELOX ambulatory chemotherapy at Ordos Central Hospital, China, from June 2021 to December 2024. Patients receiving active nutrition and exercise intervention were defined as the intervention group, and those receiving conventional standard treatment were the control group. Compare the differences in each indicator between the two groups at the two time points before and after the intervention. Nutritional intake was assessed using the Brief Conghua scale. Nutritional management was based on the five-step nutrition program recommended in the Chinese Cancer Nutrition Treatment Guidelines 2020. The exercise program was based on FITT(frequency, intensity, time, and type) mode. WeChat was used to provide patients with education and technical guidance. Neutropenia was graded according to the Common Terminology Criteria for Adverse Events version 5.0.ResultsDynamic follow-up was completed in 77 patients, including 39 in the intervention group and 38 in the control group. The intervention group showed a positive change in the L3SMI compared to that in the control group (P = 0.0032). The SMI remained stable or increased in 64.1% (25/39) of patients in the intervention group and 31.6% (12/38) in the control group. The incidence of grade ≥3 neutropenia in the intervention group was lower than that in the control group (P = 0.0011).ConclusionActive nutrition and exercise intervention can improve L3SMI and reduce the incidence of grade ≥3 neutropenia in patients with gastric cancer receiving SOX/XELOX ambulatory chemotherapy.